Rare Earth Elements Geochemistry of the Upper Oligocene-Middle Miocene Succession in the Western Iraq - Awadh, Salih; Hussien , Sfoog (Iraqi Journal of Science, 2025)
Rare earth element (REE) in the Upper Oligocene-Middle Miocene succession represented by reefal carbonate rocks of Anah Formation, dolomitic limestone of the Euphrates Formation, and gypsiferous marly limeatone of Fatha Formation in the western Iraq were used as geochemical indicators. The objectives of this study are to describe the REE patterns in the different depositional environments, and clarify their response to the diagentic processes, in particular, dolomitization. The general trend of REE pattern shows similarity for Anah and Fatha Formations, with less similarity in the Euphrates Formation. The reefal limestone facies of Anah Formation was characterized by relative depletion in REE, while REEs enrichment were distinctive character of the gypsiferous marly limestone facies in Fatha Formation. The dolomitic limestone facies belonged to the Euphrates Formation was marked with an intermediate amount of REE. The normalized ΣLREEs in the Anah and Fatha Formations have a significant variation. Furthermore, they are less abundance than the normalized ΣHREEs, with the exception of the Euphrates Formation, which suffered a relatively depleted of the ΣHREEs due to dolomitization. The negative anomaly in cerium (Ce), positive anomalies of the europium (Eu) and lanthanum (La) in the PAAS-normalized REE patterns reflect well-oxygenated shallow water of Anah and Fatha Formations; and also indicate incorporation of REE into the limestone of Euphrates Formation occurred in moderately marine deep water. The vast majority of the REEs concentration was adsorped with clay minerals rather than in carbonate rocks and gypsum. Dolomitization clearly affected the real signature of the REE, particularly, in the Euphrates Formation and provided useful information on the composition of diagenetic fluids which later became relatively depleted in HREEs as it is clear in the Euphrates Formation